2018
DOI: 10.1152/ajprenal.00601.2017
|View full text |Cite|
|
Sign up to set email alerts
|

Transcription factor HNF1β regulates expression of the calcium-sensing receptor in the thick ascending limb of the kidney

Abstract: Mutations in hepatocyte nuclear factor 1β (HNF1β) cause autosomal dominant tubulointerstitial kidney disease (ADTKD-HNF1β), and patients tend to develop renal cysts, maturity-onset diabetes of the young (MODY), and suffer from electrolyte disturbances, including hypomagnesemia, hypokalemia, and hypocalciuria. Previous HNF1β research focused on the renal distal convoluted tubule (DCT) to elucidate the ADTKD-HNF1β electrolyte phenotype, although 70% of Mg is reabsorbed in the thick ascending limb of Henle's loop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 50 publications
0
21
0
1
Order By: Relevance
“…It is important to notice that mutations in UMOD, MUC1, and HNF1B are responsible for ADTKD, showing a strict correlation between these proteins and RCAD along with ADTKD phenotypes 42 . Considering the acknowledged role of HNF1B in regulating kidney transports and also calcium-sensing receptor CaSR 16,43 , it was interesting to notice that several peptides associated with calcium binding or calcium regulating properties might be changed in RCAD patients. The disruption of multiple calcium regulators may be one of the bases of the renal cysts formation as observed previously 44,45 .…”
Section: Discussionmentioning
confidence: 99%
“…It is important to notice that mutations in UMOD, MUC1, and HNF1B are responsible for ADTKD, showing a strict correlation between these proteins and RCAD along with ADTKD phenotypes 42 . Considering the acknowledged role of HNF1B in regulating kidney transports and also calcium-sensing receptor CaSR 16,43 , it was interesting to notice that several peptides associated with calcium binding or calcium regulating properties might be changed in RCAD patients. The disruption of multiple calcium regulators may be one of the bases of the renal cysts formation as observed previously 44,45 .…”
Section: Discussionmentioning
confidence: 99%
“…Second, expression of CaSR is regulated by the transcription factor HNF1B: Using promoter assays Kompatscher et al, showed an increase in CaSR expression in presence of HNF1beta and a decrease of its expression when the DNA binding was blocked. They also observed a down regulation of the CaSR as well as of claudin-19 and of claudin-10b in hnf1b-knockout mice [69]. This likely contributes to the tubular phenotypes observed in patients with HNF1B mutations.…”
Section: Other Physiopathologies Resulting From Tal Dysfunctionmentioning
confidence: 86%
“…35 Transcriptional targets of HNF1β in the TAL involved in electrolyte transport and cystogenesis are calcium-sensing receptor (CASR), PKHD1 and KCNJ16. 4,6,45 In the DCT, FXYD2 and KCNJ16 are the main transcriptional targets. Interestingly, while both PCBD2 and PCBD1 are expressed in the DCT, our luciferase experiments show that PCBD1 enhances the activation of the FXYD2 promoter by HNF1β while PCBD2 does not.…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptional targets of HNF1β in the TAL involved in electrolyte transport and cystogenesis are calcium‐sensing receptor (CASR), PKHD1 and KCNJ16 4,6,45 . In the DCT, FXYD 2 and KCNJ16 are the main transcriptional targets.…”
Section: Discussionmentioning
confidence: 99%